Text sets : multimodal learning for multicultural students - Dowdy, Joanne Kilgour; Fleischaker, Rachael (Brill Sense, 2018)
Text Sets: Multimodal Learning for Multicultural Students integrates a multicultural approach to teaching with standards-based instruction and multimodal learning opportunities in a variety of content areas. This unique combination allows teachers to meet the demands of their curriculum while recognizing and honoring the diverse students in their classroom. Each chapter provides an annotated text set with a specific theme, curricular goals, and instructional activities that suggest ways for students to interact with the texts. In addition to providing ready-made text sets, it models a framework for teachers to build their own text sets based on the individual needs of their schools and communities.